2021
DOI: 10.1177/15353702211024651
|View full text |Cite
|
Sign up to set email alerts
|

Identification of SARS-CoV-2 on the ocular surface in a cohort of COVID-19 patients from Brazil

Abstract: In this cross-sectional study, we investigate the presence of Severe Acute Respiratory Syndrome Coronavirus 2 Ribonucleic Acid (SARS-CoV-2 RNA) in the tears of hospitalized COVID-19 patients. After laboratory confirmation of SARS-CoV-2 infection by reverse transcription polymerase chain reaction (RT-PCR) analysis, tear samples from both eyes of each patient were collected using conjunctival swab for RT-PCR. Detailed demographic profile, systemic and ocular symptoms, comorbidities, clinical, ancillary, and ocul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Clinical studies have reported that the time required for ocular manifestation varied from 15 days to two months after the infection or symptom onset 8 , 62 . Moreover, Colavita et al detected viral RNA in the ocular swabs with lower Ct values than those in the nasal swabs of a patient with COVID-19 who suffered from ocular manifestations between 21 and 27 days from the onset of symptoms 63 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical studies have reported that the time required for ocular manifestation varied from 15 days to two months after the infection or symptom onset 8 , 62 . Moreover, Colavita et al detected viral RNA in the ocular swabs with lower Ct values than those in the nasal swabs of a patient with COVID-19 who suffered from ocular manifestations between 21 and 27 days from the onset of symptoms 63 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a cross-sectional study in Italy reported the presence of viral RNA in the conjunctival swabs of 52 of 91 patients with COVID-19, with a high rate of detection in patients with severe disease 6 . Other cross-sectional studies in China 7 and Brazil 8 , and post-mortem examinations 9 , 10 also reported viral RNA detection in conjunctival swabs or in the aqueous humour of patients with or without ocular manifestations.…”
Section: Introductionmentioning
confidence: 91%
“…Clinical studies have reported that the time required for ocular manifestation varied from 15 days to two months after the infection or symptom onset (Gasparini et al, 2021;Yan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have reported that the time required for ocular manifestation varied from 15 days to two months after the infection or symptom onset (Gasparini et al, 2021; Yan et al, 2020). Moreover, Colavita et al detected viral RNA in ocular swabs with lower Ct values than those in nasal swabs between 21 and 27 days from the symptom onset of a patient with COVID-19 who suffered from ocular manifestations (Colavita et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation